Crop Production on Hillside Using Non-Bench Terracing Alternative Measures for Soil Conservation. First Year's Results of the Olive River Soil Conservation Studies - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
120 Páginas. Series pub. V-13.